2018
DOI: 10.3389/fnins.2018.00884
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and Non-invasive Stimulation of the Obese Human Brain

Abstract: Accumulating evidence suggests that non-invasive and invasive brain stimulation may reduce food craving and calorie consumption rendering these techniques potential treatment options for obesity. Non-invasive transcranial direct current stimulation (tDCS) or repetitive transcranial magnet stimulation (rTMS) are used to modulate activity in superficially located executive control regions, such as the dorsolateral prefrontal cortex (DLPFC). Modulation of the DLPFC’s activity may alter executive functioning and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 147 publications
0
9
0
1
Order By: Relevance
“…Essential to the downregulation of high-energy food reward, this region has been shown to be critical for dietary self-control ( 82 ). Thus, considered as a key node of eating behavior control, the dorsolateral PFC has been the subject of numerous brain stimulation studies, showing that increased activation of this region allowed an improvement of resistance to food stimuli ( 38 ). In the same vein, higher levels of activity in the dorsolateral PFC were shown to be a good predictor of diet success in obese individuals ( 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential to the downregulation of high-energy food reward, this region has been shown to be critical for dietary self-control ( 82 ). Thus, considered as a key node of eating behavior control, the dorsolateral PFC has been the subject of numerous brain stimulation studies, showing that increased activation of this region allowed an improvement of resistance to food stimuli ( 38 ). In the same vein, higher levels of activity in the dorsolateral PFC were shown to be a good predictor of diet success in obese individuals ( 83 , 84 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent brain stimulation studies provided promising results on the control of food craving and food intake ( 38 ). Specifically, studies showed that modulating the dorsolateral prefrontal cortex ( 39 , 40 ), nucleus accumbens ( 41 ), and hypothalamic area ( 42 ) substantially reduced food craving.…”
Section: Introductionmentioning
confidence: 99%
“…While results are mixed, animal model research generally demonstrates decreased food intake and decreased weight gain with VNS (Pelotand Grill 2018; Yao et al 2018). Research in humans has demonstrated greater weight loss for participants receiving vagal nerve block compared to sham (Ikramuddin et al 2014), including sustained weight loss over 18 months (Shikora et al 2015;Pleger 2018). Research in humans has also demonstrated a reduction in appetite and body weight with noninvasive VNS as well (Ruiz-Tovar and Llavero 2016; Pleger 2018).…”
Section: The Vagus Nerve and Obesitymentioning
confidence: 99%
“…Moreover, NBS of cortical areas as DLPFC, that has been explored in migraine, was found to be effective for treatment of other conditions, that are comorbid with disease, sharing also a stimulation target employed for migraine treatment, like DLPFC. Among these disorders, in addition to the role played by the psychiatric diseases, of particular importance is obesity which also favors the chronification of migraine (35, 36). Due to the large prevalence of the disease and the disability associated with it, and also considering the parents' relevant fears and concerns regarding pharmacological therapies, especially for continuing preventive treatment, pediatric migraine appears to be an optimal candidate for future studies on therapeutic NIBS.…”
Section: Potential Strategies For Tms and Tdcs Application In Pediatrmentioning
confidence: 99%